Win/loss reviews : a new knowledge model for competitive intelligence - Marcet, Rick (Hoboken, N.J. : John Wiley & Sons, 2011)
'An essential guide to establishing a competitive position by learning from past dealsDealing with tapping into one of the most underutilized sources of business intelligence?the collection of opportunities that have gone through sales processes?this book provides a proven methodology to winning sales via strong business intelligence. Explains how to strategically look at deals Examines how to cut through the various biases that take place when a deal is completed Presents independent perspectives from some of today's leading thinkers on the way IT innovations are transforming how organizations operate and how people work Showing how every company can achieve success through their business intelligence?the win/loss records of their deals, Win/Loss Reviews presents a methodology for reviewing sales wins and losses so that better performance and customer satisfaction can be accomplished'--
Includes bibliographical references and index.
Keywords: Marketing -- Evaluation; Business intelligence; Strategic planning; Competition